Environmental safety aspects of using the digestate from an agricultural biogas plant - Witorożec, Agata; Kopiński, Jerzy; Woźniak, Marek; Markowska-Strzemska, Ewa (Polish Journal of Agronomy, 2023)
This review aims to summarize research findings andprovide an up-to-date assessment of the current state of knowledgeon the environmental safety of digestate, including its effectson soil, crop yields and animal health. Topics covered include thepotential benefits and drawbacks of using digestate as a fertilizer.In recent years, the biogas industry in Europe has experiencedsignificant growth. Many countries are actively promoting biogasproduction as a means to reduce greenhouse gas emissionsand achieve renewable energy targets. As a result, there has beena corresponding increase in the production of digestate remainingafter the anaerobic digestion of organic waste. Digestate isa source of growing concern due to its potential adverse effectson the environment, specifically concerning soil quality and therisk of nutrient runoff. A number of studies have been conductedin European countries to assess the safety of digestate for the environmentand identify ways to reduce its negative impact.